Interactions between Saccharomyces cerevisiae and Hanseniaspora guilliermondii: cell-cell contact mechanism - Branco, Patricia (2014)
Several studies have shown that the early death of non-Saccharomyces during wine fermentations are due to yeast-yeast interactions induced by Saccharomyces cerevisiae (Sc) through different mechanisms such as growth arrest mediated by a cell-cell contact mechanism (Nissen et al. 2003) and death mediated by killer-like toxins (Pérez-Nevado et al 2006; Albergaria et al. 2010). Besides, previous work also showed that death of non-Saccharomyces in co-cultivation with Sc is always triggered at the end of exponential growth phase (Pérez-Nevado et al 2006). In order to investigate the role of cell-cell contact in the early death of non-Saccharomyces, we performed assays in which Sc cells pre-grown at enological growth conditions for 12 and 48 h, respectively, were in direct contact with Hanseniaspora guilliermondii (Hg) cells at high cellular density (107-108 cells/ml) in a carbon-free medium. As a negative control we performed similar assays in which Sc and Hg cells were separated by a dialysis tube (pore cut-off of 1000 kDa) and as a positive control a single Hg culture. Results showed that Hg cell density decreased by 2 orders of magnitude (i.e. from 108-106 cells/ml) in contact with 48 h-grown Sc cells, while its viability remained unchanged (108cfu/ml) in the presence of 12 h-grown Sc cells. Moreover, Hg viability was not affected both in the dialysis tube experiments and single culture, which confirmed the death-induced cell-cell contact phenomenon.